Behavioral finance and decision-making models - Tripathi, Tripti, 1982-; Dash, Manoj Kumar; Agrawal, Gaurav, 1977- (Advances in finance, accounting, and economics (AFAE) book series., 2019)
"This book examines behavioral biases and their impact on investment decisions. It also explores the applicability of econometric data modelling in behavioral finance markets and financial innovations in various fields of micro finance, public private partnership, mergers and acquisitions and behavioral finance"--